Typologies of Peri-Urban Klaten-Central Java: A study based on Socio-Economic Perspective - Yesiana, Reny (Department of Urban and Regional Planning, Diponegoro University, 2014)
Abstract: Urbanization as a socio-economic change in developing countries has been leading to the existence of a region with a mixture of rural and urban character so called Peri-Urban Areas (PUA). PUA has been emerging as a part of urban growth process as well as rural growth, regarded as rural-urban transition. This phenomenon could be clearly observed in Klaten District, Central Java Province. Located between two strategic cities in Central Java, i.e. Yogyakarta and Surakarta, Klaten has been experiencing a significant land conversion (among the highest in the province) and a significant economic growth in comparison to other districts in the province. Accordingly, Klaten was chosen as the case study to understand the PUA development in Central Java. By focusing on socio-economic perspective, this paper aims to determine PUA typology in Klaten and further analyze the driving factors of the emerging PUA typology. Quantitative analysis using GIS tools and scoring method was applied to create the typology based on secondary socio-economic data taken from statistics report. As the results of the analysis, it has been shown that most of villages in the study area are highly rural in terms of social character. On the contrary, in economic aspect such as employment, the PUA of Klaten community has a strong urban character. It is classified as the fourth typology (highly rural in social character and highly urban in economic character) among the four identified PUA typologies in Klaten. The underlying influential factor of the development of PUA in Klaten is very much its local potential, i.e. the local economic activity. This may provide an evidence that urban and rural growth could be taken place as a part of âlocalâ growth which does not necessarily take place as a part of urban growth (expansion) of the main city (growth center).Keywords: Urbanization, Peri-Urban, Klaten